Protective Effects of Centella Asiatica Leaf Extract Cream on IL-1α Expression and Sunburn Cells in BALB/c Mice Induced by UVB - Sari, Libia; Mawardi, Prasetyadi; Subchan, Prasetyowati (Scripta Medica, 2025)
Background/Aim: UVB radiation can induce DNA damage in keratinocyte cells, leading to increased levels of reactive oxygen species (ROS) triggered by the release of proinflammatory cytokine IL-1α and apoptosis (sunburn) of keratinocyte cells. Centella asiatica (C asiatica) leaf extract contains various secondary metabolites such as flavonoids, alkaloids, tannins and saponins, which have been proven to have antioxidant and anti-inflammatory activities. This study aimed to analyse the effect of C asiatica leaf extract cream on the expression of IL-1α and sunburn cells in acute UVB-induced BALB/c mice.Methods: Experimental research was designed with a post-test control group of 4 groups: normal control group, negative control, 10 % C asiatica leaf extract cream group (P1) and 20 % C asiatica leaf extract cream group (P2). Each mouse was exposed to UV-B light broadband at a dose of 1 minimal erythema dose (MED) or energy 360 mJ/cm² from day 1 to day 5 for 6 minutes with a distance of 30 cm, while the standard group was not exposed to UVB. In P1 and P2, C asiatica leaf extract cream of 10 % and 20 % was applied daily for 5 days, while the negative control received base cream. On day 6, skin tissue samples were taken and analysis was performed for IL-1α expression using immunohistochemistry (IHC) and sunburn cells using haematoxylin and eosin staining.Results: The expression of IL-1α in the treatment groups decreased with increasing doses, with P2 having IL-1α expression (43.33 ± 7.60), P1 (48.33 ± 8.33), negative control (69.17 ± 9.17) and standard control (50.00 ± 1.91). The number of sunburn cells also decreased in the P1 (1.08 ± 0.15) and P2 (1.20 ± 0.19) groups compared to the negative control group (1.48 ± 0.17).Conclusion: The administration of C asiatica leaf extract cream can reduce the expression of the IL-1α gene and the number of sunburn cells in the skin tissue of mice induced by acute UVB radiation.
Keywords: Centella asiatica; Interleukin-1alpha; Sunburn; Ultraviolet rays; UVB